1997
DOI: 10.1128/aac.41.10.2265
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread detection of PER-1-type extended-spectrum beta-lactamases among nosocomial Acinetobacter and Pseudomonas aeruginosa isolates in Turkey: a nationwide multicenter study

Abstract: We studied the prevalence and molecular epidemiology of PER-1-type beta-lactamases among Acinetobacter, Klebsiella, and Pseudomonas aeruginosa strains isolated over a 3-month period in eight university hospitals from distinct regions of Turkey. A total of 72, 92, and 367 Acinetobacter, Klebsiella, and P. aeruginosa isolates were studied, respectively. The presence of blaPER was determined by the colony hybridization method and later confirmed by isoelectric focusing. We detected PER-1-type beta-lactamases in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(96 citation statements)
references
References 30 publications
1
89
0
6
Order By: Relevance
“…These enzymes hydrolyse penicillins (with the exception of cefepime and carbapenems) as well as narrow-spectrum and extendedspectrum cephalosporins. In addition to AmpC, Class A ␤-lactamases have been isolated (such as TEM-I type and SHV type) as well as ESBLs such as PER-1, an enzyme very prevalent in A. baumannii strains mostly in Turkey and Korea, and VEB-1, which has caused outbreaks in French and Belgian hospitals [58][59][60][61][62]. In addition, SHV-12, TEM-92, TEM-116 and CTX-M-2 have been reported from China, Italy, The Netherlands and Japan, respectively [2].…”
Section: β-Lactamasesmentioning
confidence: 99%
“…These enzymes hydrolyse penicillins (with the exception of cefepime and carbapenems) as well as narrow-spectrum and extendedspectrum cephalosporins. In addition to AmpC, Class A ␤-lactamases have been isolated (such as TEM-I type and SHV type) as well as ESBLs such as PER-1, an enzyme very prevalent in A. baumannii strains mostly in Turkey and Korea, and VEB-1, which has caused outbreaks in French and Belgian hospitals [58][59][60][61][62]. In addition, SHV-12, TEM-92, TEM-116 and CTX-M-2 have been reported from China, Italy, The Netherlands and Japan, respectively [2].…”
Section: β-Lactamasesmentioning
confidence: 99%
“…However, acquired metallo-␤-lactamase (MBL) enzymes, which confer resistance to the carbapenems, have been reported [4]. Recent reports have shown that MBLs, such as PER-1, VIM-2 and IMP-1, are prevalent in Turkey and Korea and are a growing source of resistance in these countries [5,6]. The dissemination of the OXA-23 and OXA-58 carbapenemases among A. baumannii isolates has also been reported in hospitals in Argentina [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…The clinical relevance of multidrug-resistant A. baumannii has recently been stressed by reports of nosocomial infection in Europe and Korea. 2,4,9,22,23 Our report indicates that the bla PER-1 gene may be becoming an emerging therapeutic problem in Korea.…”
Section: Discussionmentioning
confidence: 90%